Grammatical Cohesion Found in Recount Texts of “Pathway to English” X Grade Curriculum 2013 General Program by Erlangga - Hanita Masithoh; Sayyidatul Fadlilah (Vision: Journal for Language and Foreign Language Learning, 2017)
The role of a textbook in the teaching-learning process is significant since most teachers used it as the source and guidance of teaching materials. In order to know the quality of the textbooks, the teachers should be able to analyze the materials contained inside because the selection of the textbooks determines the quality of the materials which will be delivered to the students. This study aimed to find out the grammatical cohesion of recount text in Pathway to English; English textbook for the tenth grade of senior high school published by Erlangga. The design of this study is a qualitative study using literature review as an approach. The study found that there are three recount texts in Pathway to English. Text 1 and 3 contained three types of grammatical cohesion (reference, ellipsis, conjunction).  Text 2 contained complete grammatical cohesion (reference, substitution, ellipsis, conjunction). This textbook categorizes as objective criteria because the percentage of grammatical cohesion is 33%.